The Effect of Lactation Massage on Breast Milk Production in Postpartum Mothers at The PAMC Garut Clinic - Suryani, Naning (Nursing Case Insight Journal, 2024)
Mother's Breast milk is the best food for babies. Stage I breast milk starts from the first day to the fourth day which is colostrum. Colostrum is very important for the baby's body defense because colostrum is the first immunization for babies. Ideally, the breastfeeding process can be done as soon as the baby is born. However, the reality in the field shows that the production and ejection of breast milk is small in the first days, so that many mothers experience ineffectiveness in the breastfeeding process, which becomes an obstacle, namely low milk production. Lactation massage is a massage to stimulate the release of breast milk. Lactation massage can provide a feeling of comfort to post-partum mothers by providing a gentle touch to the mother through lactation massage which can stimulate the oxytocin reflex which can increase breast milk production. The aim of this study was to determine the effect of lactation massage on accelerating breast milk production in post-partum mothers. This research uses a qualitative method with a case study approach.  The instrument that will be used in this research is an observation sheet to determine the acceleration of breast milk production by respondents. When compared to those who did not receive a massage for longer than two days, the respondent who received a massage produced more breast milk. Postpartum mothers are advised to use this technique to produce more breast milk.